Measuring blunt force head impacts in athletes - Bartsch, A.; Dama, R.; Alberts, J.; Samorezov, S.; Benzel, E.; Miele, V.; Shah, A.; Humm, J.; McCrea, M.; Stemper, B. (Military Medicine, 2020)
Although concussion continues to be a major source of acute and chronic injuries, concussion injury mechanisms and risk functions are ill-defined. This lack of definition has hindered efforts to develop standardized concussion monitoring, safety testing, and protective countermeasures. To overcome this knowledge gap, we have developed, tested, and deployed a head impact monitoring mouthguard (IMM) system. Materials and Methods: The IMM system was first calibrated in 731 laboratory tests. Versus reference, Laboratory IMM data fit a linear model, with results close to the ideal linear model of form y = x + 0, R2 = 1. Next, during on-field play involving n = 54 amateur American athletes in football and boxing, there were tens of thousands of events collected by the IMM. A total of 890 true-positive head impacts were confirmed using a combination of signal processing and National Institute of Neurological Disorders and Stroke/National Institutes of Health Common Data Elements methods. Results: The median and 99th percentile of peak scalar linear acceleration and peak angular acceleration were 20 and 50 g and 1,700 and 4,600 rad/s2, respectively. No athletes were diagnosed with concussion. Conclusions: While these data are useful for preliminary human tolerance limits, a larger population must be used to quantify real-world dose response as a function of impact magnitude, direction, location, and accumulation. This work is ongoing.